2015
DOI: 10.1021/acsmedchemlett.5b00357
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Nonpeptide Inhibitors of Hepatocyte Growth Factor Activation

Abstract: In this letter we report first nonpeptide inhibitors of hepatocyte growth factor (HGF) activation. These compounds inhibit the three proteases (matriptase, hepsin, and HGF activator) required for HGF maturation. We show that 6, 8a, 8b, and 8d block activation of fibroblast-derived pro-HGF, thus preventing fibroblast-induced scattering of DU145 prostate cancer cells. Compound 6 (SRI 31215) is very soluble (91 μM) and has excellent microsome stability (human t 1/2 = 162 min; mouse t 1/2 = 296 min). In mouse 6 ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…The design of SRI 31215 (Figure 1A ) was based upon a structural template adapted from inhibitors of clotting factor Xa [ 44 , 45 ]. Details of the structure-based design effort have been reported elsewhere [ 46 ]. We demonstrated that SRI 31215 is an equipotent inhibitor of matriptase (IC 50 = 0.69 μM), hepsin (IC 50 = 0.65 μM) and HGFA (IC 50 = 0.3 μM) (Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The design of SRI 31215 (Figure 1A ) was based upon a structural template adapted from inhibitors of clotting factor Xa [ 44 , 45 ]. Details of the structure-based design effort have been reported elsewhere [ 46 ]. We demonstrated that SRI 31215 is an equipotent inhibitor of matriptase (IC 50 = 0.69 μM), hepsin (IC 50 = 0.65 μM) and HGFA (IC 50 = 0.3 μM) (Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…We demonstrated that SRI 31215 is an equipotent inhibitor of matriptase (IC 50 = 0.69 μM), hepsin (IC 50 = 0.65 μM) and HGFA (IC 50 = 0.3 μM) (Figure 1A ). While the selectivity of SRI 31215 for trypsin and thrombin is acceptable, currently we are optimizing its selectivity over factor Xa [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The HGF-MET cascade is considered a key target for inhibiting cancer metastasis (Mizuno and Nakamura, 2013). The proteolytic conversion of pro-HGF to active HGF is the rate-limiting step in this signaling cascade (Venukadasula et al, 2015) and, therefore, is a primary target on current approaches to preventing HGF/MET signaling.…”
Section: Introductionmentioning
confidence: 99%
“…HAI-1 and HAI-2 are synthesized as type-1 transmembrane glycoproteins and both have two Kunitz-type serine protease domains, the first of which is thought to be responsible for the HGFAinhibitory activity (Berger, 2002;Parr et al, 2004). The balance between these inhibitors and serine proteases is a critical factor in HGF activation in tumors (Parr and Jiang, 2006;Venukadasula et al, 2015). HAI-1 is a suggested marker of prostate epithelial cell proliferation (Warren et al, 2009), and a favorable prognostic marker of prostate cancer (Nagakawa et al, 2006;Yasuda et al, 2013;Hu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%